Protecting the freedom of speech in university campuses: A sight at the offensive speech rom the american experience - Pérez, Rodrigo Pablo (Derecho Público Iberoamericano, 2020)
The present article exposes an insight of the American case law about freedom of speech in universities and colleges. It is a topic that is becoming contested in Chile. The experience, where the freedom of speech has been strongly protected, is a relevant source for analyzing the route that Chilean Courts must follow.